Incidence of Cefixime Resistance in Patients with Chronic Kidney Disease at Harapan Keluarga Hospital - Theresia, Yulia Dian; Ansyori, Maz Isa; Maulana, Akhada; Wedayani , Anak Agung Ayu Niti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Antibiotic resistance is an increasing global health challenge, especially in patients with advanced chronic kidney disease (CKD). This study aims to investigate cefixime resistance in patients with stage 4-5 CKD at Harapan Keluarga Hospital with a retrospective cohort design using medical record data. Chi-squared test analysis showed a significant association between cefixime resistance and advanced CKD (χ² = 34.714, p = 0.003). The results showed a higher prevalence of cefixime resistance in male patients (60%), antibiotic use of more than 14 days (65%), and hospitalization of more than five days (80%). The mechanism of resistance involves beta-lactamase production and changes in the gut microbiota due to dysbiosis. Factors such as irrational antibiotic use, length of hospital stay, and catheter use contributed to higher resistance. This study highlights the need for evidence-based antibiotic stewardship strategies to reduce resistance, especially in vulnerable populations such as patients with advanced CKD. Scientific implications include the development of more effective infection management strategies, close monitoring of antibiotic use, dose adjustment according to CKD severity, and education of health care workers to increase awareness of antibiotic resistance. This study contributes to efforts to prevent antibiotic resistance in the advanced CKD population.